THE INFLUENCE OF SERVICE QUALITY, FACILITIES, AND PRICE ON PATIENT SATISFACTION AT HASNA MEDIKA CLINIC BANDUNG - Lia Mulyawati; Erika Nurmartiani; Rulia; Kosasih; Vip Paramarta (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the effect of service quality, facilities, and price on patient satisfaction at Hasna Medika Clinic Bandung. The research employs a quantitative method with a descriptive and verificative approach. Data were collected through questionnaires distributed to 315 patients, selected using the Slovin formula. The data analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing (t-test and F-test). The results show that partially, service quality, facilities, and price have a positive and significant effect on patient satisfaction. Among these variables, price is identified as the most dominant factor influencing satisfaction, followed by service quality and facilities. Simultaneously, the three variables significantly affect patient satisfaction, as indicated by the F-test results. The coefficient of determination (R²) value of 0.710 indicates that 71% of the variation in patient satisfaction can be explained by service quality, facilities, and price, while the remaining 29% is influenced by other factors outside the model. These findings suggest that improving service quality, maintaining adequate facilities, and implementing competitive and transparent pricing strategies are essential to enhance patient satisfaction. Therefore, Hasna Medika Clinic Bandung is recommended to continuously optimize these aspects to increase patient loyalty and competitiveness in the healthcare sector.